2022
DOI: 10.1177/08959048221087210
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Being “Woke”: Charter Management Organizations and the Growth of Social Consciousness as a School Quality Marker

Abstract: Charter management organizations (CMOs) have increasingly had to respond to questions surrounding their organizations—particularly in the context of the broader social awakening around systemic injustices and evidence of their racially inequitable practices. This study investigated how CMOs counteracted criticisms and managed perception by characterizing their organizations as socially and racially conscious. It compared social media content for one CMO population during two time periods that surround the 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…It seems likely, however, that the findings are applicable to many other communities across the United States and elsewhere who are attempting to create inclusionary environments. Voluntary and intentional integration and school-based integration are on the rise (Potter & Burris, 2020), as are discussions of racial inequality and institutional racism, especially in the context of schools (Hernández, 2022). Furthermore, discussions of transgender youth’s rights and conflicts over gender-unlabeled bathrooms are increasingly prominent in public and educational discourse (Martino et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems likely, however, that the findings are applicable to many other communities across the United States and elsewhere who are attempting to create inclusionary environments. Voluntary and intentional integration and school-based integration are on the rise (Potter & Burris, 2020), as are discussions of racial inequality and institutional racism, especially in the context of schools (Hernández, 2022). Furthermore, discussions of transgender youth’s rights and conflicts over gender-unlabeled bathrooms are increasingly prominent in public and educational discourse (Martino et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While we know a great deal about the exclusionary experiences of students of color and low-income students and their families in integrated schools and the structural underpinnings of these experiences, there is much to be learned, from both a theoretical and a practical perspective, about the mechanisms connecting racialized structures with exclusionary experiences, especially in the context of growing attention to racial inequality and the burgeoning of voluntary, bottom-up, school integration (Hernández, 2022; Potter & Burris, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies show that in making the case for their schools, CMOs have been shown to derogate Black and Latinx communities by characterizing them as crisis-laden and suggest that students come to CMO schools with dispositions that require behavioral, cultural, and educational rehabilitation (Hernández, 2016). Conversely, studies show that CMOs increasingly characterize their organizations as socially conscious, though they project a bounded version of racial equity that provides cover for neoliberal reform to persist (Hernández, 2022b).…”
Section: The Racialized Character Of Cmosmentioning
confidence: 99%
“…In the United Kingdom, for example, the Academies Programme managed 7,000 state-funded schools that did not have to hire teachers with Qualified Teacher Status (Martindale, 2019). Similar things happen in other countries like the friskolor in Sweden, charter management organizations in the United States, and voucher programs in Chile (Hernández, 2022;Hofflinger & von Hippel, 2020;Martindale, 2019). Panel C illustrates how direct support organizations and research/advocacy organizations receives funding from both private philanthropy and public education offices, a dynamic criticized for funneling taxpayer dollars away from traditional public institutions (i.e., neighborhood schools).…”
mentioning
confidence: 94%
“…For organizations that directly support schools, we suggest a continuum between those that provide long-term wrap-around management services and those that provide ad hoc supports like annual trainings and professional development. Examples of organizations that more closely relate to the former include education or charter management organizations since they often have longterm contracts where they manage the operations in the school and scale practices among their schools (Hernández, 2022). Examples of organizations that relate to the latter include professional associations and leadership development trainings.…”
mentioning
confidence: 99%